Low‐Field MRI and Multislice CT for the Detection of Cerebellar (Foramen Magnum) Herniation in Cavalier King Charles Spaniels. (19th November 2014) - Kromhout, K.; van Bree, H.; Broeckx, B.J.G.; Bhatti, S.; Van Ham, L.; Polis, I.; Gielen, I.
<x xml:space="preserve">Abstract</x> Background Cavalier King Charles Spaniels (CKCS) have a high prevalence of Chiari‐like malformation (CM). Herniation of the cerebellum into the foramen magnum is a key diagnostic feature for CM. Midsagittal MR images are the preferred technique for visualizing cerebellar herniation (CH). Objective To investigate whether CT can be used to diagnose CH. Animals Fifteen client‐owned CKCS dogs referred for investigation of the brain and cranial cervical spine on MRI and CT. Methods Two reviewers retrospectively analyzed midsagittal T1WSE and T2WSE MR images and midsagittal pre‐ and postcontrast 2D multiplanar reformatted CT images from each dog for the presence of CH. And, if present, the length (mm, CHL) of the herniation was measured. The results were analyzed statistically. Results There was no significant difference between the different observers and techniques for the detection of CH and measurement of CHL. Overall, the CHL was longer on the CT images. Conclusion and Clinical Importance Both techniques are useful for detecting CH and measuring CHL. Because CHL does not have a known direct impact on the clinical presentation of CM, CT can be used as a diagnostic tool in a routine clinical practice for CM in CKCS when MRI is not available. We emphasize that MRI is the standard screening technique in CKCS for breeding purposes to detect the presence of CM and SM and, at the current time, CT cannot replace MRI.